Why Is China Investing in Africa? Evidence from the Firm Level - Chen, Wenjie (Published by Oxford University Press on behalf of the World Bank, 2020)
China’s increased trade with, and investment in, Africa have boosted the continent’s economic growth but have also generated considerable controversy. The aggregate data on China’s overseas direct investment (ODI) in African countries reveal that China’s share of the stock of foreign investment is small, though growing rapidly. China’s attraction to resource-rich countries is no different from Western investment. China’s overall ODI is uncorrelated with a measure of rule of law, whereas Western investment favors the better governance environments. As a result, Chinese investment in strong and weak governance environments is about the same, but its share of foreign investment is higher in the weak governance states. Micro data from MOFCOM’s database on registered Chinese firms investing in Africa between 1998 and 2012 provide a different perspective. Key words in project descriptions are used to code the investments into 25 sectors. This database captures the small and medium private firms investing in Africa. Contrary to common perceptions, there are few projects in natural resource sectors. Most projects are in services, with a significant number in manufacturing as well. Country-sector-level regressions based on firms’ transaction-level data find that Chinese ODI, both horizontal and vertical, is profit-driven, like investment from other countries. In particular, regressions show that Chinese ODI is relatively more concentrated in skill-intensive sectors in skill-abundant countries but in capital-intensive sectors in capital-scarce countries. These patterns are mostly observed in politically unstable countries, suggesting stronger incentives to seek profits in tougher environments.